STRATEGI PENGEMBANGAN SUMBER DAYA MANUSIA DALAM MENINGKATKAN KINERJA PENDIDIK DI SMA ISLAM SHAFTA SURABAYA - Imamul Aminin, Moh. (Program Studi Pendidikan Agama Islam STIT al Urwatul Wutsqo Bulurejo Jombang, 2024)
Human resources, which function as the driving force for all activities in all fields of education, are an important component in improving the quality of education. So thatstrategies are needed to improve the performance of educator human resources. Thus, research is needed regarding the implementation and implications of human resource development strategies in improving the performance of educators at Shafta Islamic High School Surabaya?This study aims to determine the implementation and implications of human resource development strategies in improving the performance of educators at SMA Islam Shafta Surabaya. This study uses a qualitative approach in which the researcher acts as the key instrument. Sampling of data sources was carried out purposively and snowball. This study aims to analyze human resource development management strategies in improving the performance of educators at Shafta Islamic High School Surabaya. Data collection is a systematic and standardized process to obtain the necessary information. Data collection techniques used are observation, interviews, and documentation. The results of this study are; 1.The human resource development strategy carried out by Shafta Islamic High School Surabaya in improving the performance of educator human resources is to create programs designed in strategic planning, approach the entire academic community, and directly supervise school institution programs. The program includes workshops, seminars, learning media development and competency development, 2. The implications of the human resource development strategy at Shafta Islamic High School Surabaya from the program implemented there are several things that have improved from a professional and pedagogic standpoint of educators.